2013
DOI: 10.1155/2013/587024
|View full text |Cite
|
Sign up to set email alerts
|

The Serological and Virological Investigation of Canine Adenovirus Infection on the Dogs

Abstract: Two types of Canine Adenovirus (CAVs), Canine Adenovirus type 1 (CAV-1), the virus which causes infectious canine hepatitis, and Canine Adenovirus type 2 (CAV-2), which causes canine infectious laryngotracheitis, have been found in dogs. In this study, blood samples taken from 111 dogs, which were admitted to the Internal Medicine Clinic of Selcuk University, Faculty of Veterinary Medicine, with clinical symptoms. Seventy-seven dogs were sampled from Isparta and Burdur dog shelters by random sampling, regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
(16 reference statements)
1
17
1
3
Order By: Relevance
“…BVDV is a major cause of reproductive failure and immunosupression, and cause substantial economic losses in livestock industries through their impact on reproduction and health. Numerous studies (Yildirim et al, 2011;Bulut et al, 2013;Erol et al, 2014) conducted with regard to the BVDV infection in Turkey have demonstrated that the infection is widespread in cattle. These studies have reported that BVDV seroprevalence varies between 14.3-100% in cattle in various regions of Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BVDV is a major cause of reproductive failure and immunosupression, and cause substantial economic losses in livestock industries through their impact on reproduction and health. Numerous studies (Yildirim et al, 2011;Bulut et al, 2013;Erol et al, 2014) conducted with regard to the BVDV infection in Turkey have demonstrated that the infection is widespread in cattle. These studies have reported that BVDV seroprevalence varies between 14.3-100% in cattle in various regions of Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship has also been reported between antibody titers in blood serum and milk serum. Yavru et al (2013) tested the blood and milk serum of 202 cows for the presence of the antibodies formed in response to BVDV using indirect ELISA, and they determined that both the blood serum and milk serum taken from 148 (73.2%) animals were consistently seropositive. Because it was determined that the ELISA antibody values for blood and milk were similar at the conclusion of the study, this established that milk serum samples could be used instead of blood serum in the serological diagnosis of BVDV Stahl et al (2002) claimed that milk samples could be used to determine BVDV antibody levels using ELISA for entire herds in cattle operations suspected of being infected with BVDV.…”
Section: Discussionmentioning
confidence: 99%
“…CAdV-1 has been reported in different fox species in several geographic areas (Thompson et al, 2010;Walker et al, 2016a,b). Serological and pathogen surveys conducted in Thailand, Scandinavia, South Africa, Italy, and Turkey demonstrate the high prevalence of CAdV-2 infections in wild dogs and red foxes (Balboni et al, 2013;Bulut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some enzyme-linked immunosorbent assay (ELISA)-based serologic tests detect antibodies to both these agents. In fact, some reports on CAV in Turkey (CAN SAHNA and ASLAN, 2015;BULUT et al, 2013) have reported information on CAV seropositivity. However, to the best of our knowledge, no studies have reported CAV-2 seroprevalence, virus isolation, or molecular epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…This virus was first detected in dogs in a Canadian shelter in 1961 that had symptoms of upper respiratory tract infection (DITCHFIELD et al, 1962). In subsequent years, the presence of CAV-2 was reported in many countries such as Italy, Brazil, and India (BALBONI et al, 2013;PARTHIBAN et al, 2009;SILVA et al, 2014) and was also detected in Turkey, based on serological data alone (BULUT et al, 2013;CAN SAHNA and ASLAN, 2015).…”
Section: Introductionmentioning
confidence: 94%